Special Issue on the Pathobiology of Laboratory Nonhuman Primates: A Review of Species, Substrain, Geographical Origin, Age, and Modality-Related Factors. (July 2022) - Chamanza, Ronnie; Amuzie, Chidozie J.; Chilton, Jennifer; Engelhardt, Jeffery A.
Nonhuman primates (NHPs) are utilized in nonclinical safety testing due to their phylogenetic proximity to humans and similarity in physiology and anatomy. However, ethical considerations and the increased demand for NHPs, coupled with the current shortage in their supply, have increased the calls to minimize their use. In addition, the increased demand and supply shortage of NHPs have increased the use of animals sourced from different geographical origins, and animals of different ages, which can complicate the interpretation of study results. Coupled with the relative uniqueness of findings induced by novel therapeutic modalities, there is an increasing need for a deeper understanding of the systemic pathobiology of NHPs. Here we provide a brief preview of the two main themes discussed in this special issue, which include the influence of geographical origin, age, and sex on background pathology, clinical pathology reference values, other relevant toxicology endpoints, and organ system pathology.